2002
DOI: 10.1152/ajpregu.00328.2002
|View full text |Cite
|
Sign up to set email alerts
|

A neurochemical mechanism for hypoxia-induced anapyrexia

Abstract: Hypoxia evokes a regulated decrease in body temperature, a response that has been termed anapyrexia, but the mechanisms involved are poorly understood. Therefore, the present study was undertaken to test the hypothesis that hypoxia-induced anapyrexia results from the activation of cAMP- and cGMP-dependent pathways in the preoptic region (PO). Adult male Wistar rats weighing 230-260 g were used. Body temperature was monitored by biotelemetry, and the levels of cAMP and cGMP were determined in the anteroventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Both traits are related since hypoxia elicits an array of compensatory responses, among them is anapyrexia, the regulated drop of body temperature, which is a very efficient way to prevent cellular damage caused by hypoxia . The general importance of anapyrexia resides in the fact that it reduces the consumption of oxygen and increases the affinity of haemoglobin to oxygen (Bicego et al, 2002;Steiner et al, 2002). Variations in temperature tend to affect the entire organism (Odehnalová et al, 2008); the neonate piglets that obtained a low vitality score showed hypercapnia, results in agreement with previous work by Randall (1971) and Herpin et al (1996); whereas more recently, Groenendaal et al (2009) indicated that hypothermia affects PCO 2 diminishing this gas concentration at low temperatures.…”
Section: Vitality: Body Temperature and Blood Gasessupporting
confidence: 83%
“…Both traits are related since hypoxia elicits an array of compensatory responses, among them is anapyrexia, the regulated drop of body temperature, which is a very efficient way to prevent cellular damage caused by hypoxia . The general importance of anapyrexia resides in the fact that it reduces the consumption of oxygen and increases the affinity of haemoglobin to oxygen (Bicego et al, 2002;Steiner et al, 2002). Variations in temperature tend to affect the entire organism (Odehnalová et al, 2008); the neonate piglets that obtained a low vitality score showed hypercapnia, results in agreement with previous work by Randall (1971) and Herpin et al (1996); whereas more recently, Groenendaal et al (2009) indicated that hypothermia affects PCO 2 diminishing this gas concentration at low temperatures.…”
Section: Vitality: Body Temperature and Blood Gasessupporting
confidence: 83%
“…A role for NO in N 2 Oaugmented heat dissipation seems plausible in part because Quock and colleagues (7,26,28) have implicated NO in other N 2 O effects, specifically its antinociceptive and anxiolytic effects. Additionally, because hypoxia-induced hypothermia is attenuated by microinjection of a NO synthesis inhibitor in the preoptic hypothalamus (65), it is possible that central as well as peripheral NO release could participate in mediating the hypothermic effect of N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…This response is typically seen as being protective and contributes to the preservation of arterial oxygen pressure in hypoxia. This is an active process resulting from a reduction of the thermoregulatory set point, regulated within the preoptic hypothalamic nucleus (Barros et al, 2001;Steiner et al, 2002). It is possible to ask whether the drop in rectal temperature accounted for the fall in metabolic rate or whether is there evidence of metabolic suppression beyond that due to a resetting of the body temperature set point (Barros et al, 2001).…”
Section: Respiratory and Metabolic Responses To Hypoxia In High Altitmentioning
confidence: 99%